El Veto de los" Cinco Grandes" del Consejo de Seguridad de la Organización de las Naciones Unidas - Zegarra López, Fernando Elías (2025)
The United Nations was created in 1945 with the main purpose of maintaining international peace and security, for which it was structured into six bodies, one of them, the Security Council, has a high degree of influence in the fulfillment of its purposes. Throughout its operation, the power of the five permanent members, known as the “veto”, regulated by Article 27 of the San Francisco Charter, has been questioned, which has motivated the presentation of various proposals within and outside the organization, which achieved some changes, while other initiatives persist, that’s why in this article we analyze the most notable, with the purpose of inferring the future regarding this issue of global interest, based mainly on the primacy of reality.